Demographic changes in breast cancer incidence, stage at diagnosis and age associated with population‐based mammographic screening. Issue 5 (14th February 2017) - Verdial, Francys C.; Etzioni, Ruth; Duggan, Catherine; Anderson, Benjamin O.
Abstract : BACKGROUND: Breast cancer incidence and mortality are influenced by early‐detection methods, including mammographic screening. Demographic changes in US statistics serve as a model for changes that can be anticipated in countries where mammographic screening has not been implemented. METHODS: SEER statistics (1973‐2013) for breast cancer mortality, incidence, stage at diagnosis, and age at diagnosis were examined. Temporal associations between screening changes and breast cancer demographics in the US were documented. FINDINGS: Before 1982 (pre‐screening), breast cancer incidence in the US remained stable, with similar incidence of localized and regional cancers, and with in‐situ disease comprising <2% of diagnosed disease. 1 During the transitional phase of mammographic screening, breast cancer incidence increased. In 1991, breast cancer age‐adjusted mortality rates began decreasing and have continued to decrease. In the post‐screening phase, stage distribution stabilized, but now with localized and in‐situ disease representing the majority of diagnosed cases. The median age at diagnosis has increased to 61 years. DISCUSSION: Mammographic screening increases breast cancer incidence, shifts the stage distribution toward earlier stage disease, and in high‐income countries, is associated with improved survival. Whether similar improvement in breast cancer survival can be achieved in the absence of mammographic screening has yet to be conclusively demonstrated.